Business issues and business prospects of immigrant entrepreneurs in New Zealand: an empirical analysis of Structural Equation Modelling (SEM) - Nel, Pieter; Abdullah, Moha Asri (Society for Human and Social Potential Development, 2019)
Immigrant entrepreneurs are widely perceived as being highly sought after for innovation and economic growth. This view is commonly shared by many developed countries where immigration policies favourably reflect special visas and entry programmes to attract immigrant entrepreneurs. It is also widely acknowledged that business ownership is not only higher, but also growing among the foreign-born population rather than the native-born population in a country. New Zealand is not an exception to this, as immigrants turn more frequently to self-employment and start up their own than do native-born workers. This paper seeks to examine whether a relationship between certain business issues and business prospects of immigrant entrepreneurs in a constructed Structured Equation Modelling (SEM) approach exists. This analysis is carried out on the basis of a face-to-face questionnaire survey on the 262 immigrant entrepreneurs of small retail businesses in Auckland. A step by step approach was utilised by means of a quantitative analysis starting from an exploratory factor analysis (EFA) followed by confirmatory factor analysis (CFA) to comply with the structured model. Subsequently, structural equation modelling (SEM) was used to obtain results. The finding shows that the ratio of Chi-square (x2) to the degree of freedom (df) is 2.072. The value of CFI is 0.922 and RMSEA is 0.074, satisfying the goodness of measures in the model constructed. Furthermore, the structural path (relationships) between immigrant business issues in relation to business prospects is significant (p < 0.05). The study concludes that there are specific issues or factors that positively contribute to business prospects of immigrant entrepreneurs. With the increase in the awareness of business issues which immigrant entrepreneurs are confronted with, there is a greater possibility that business prospects will also be promising. This may reflect the overall growth of small businesses in which the immigrant entrepreneurs are involved, given the possibility that they would potentially contribute to economic growth activities in New Zealand.